Access to finance for SMEs in post-socialist countries: the Baltic States and the South Caucasus compared. Issue 5 (17th June 2021) - Imarhiagbe, Bernard Owens; Smallbone, David; Saridakis, George; Blackburn, Robert; Mohammed, Anne-Marie
Abstract : Purpose: This article examines access to finance for SMEs in the Baltic States and the South Caucasus countries following the financial crisis of 2007 and is set within the context of the rule of law for businesses. Design/methodology/approach: The article uses the cross-sectional dataset from the Business Environment and Enterprise Performance Survey (BEEPS) for 2009 to examine access to finance for SMEs and the court system in the Baltic States and the South Caucasus countries. An ordered probit estimation technique is used to model access to finance and the court system in the Baltic States and the South Caucasus countries. The analysis draws upon institutional theory to explain access to finance for SMEs. Findings: The results show variations from one Baltic State and South Caucasus country to another in relation to fairness, speed of justice and enforcement of court decisions. The analysis suggests that if access to finance is not an obstacle to business operations and the court system is fair, impartial and uncorrupted, it determines the likelihood of strength in entrepreneurship. Additionally, the results show that, within the Baltic region, businesses experiencing constraints in accessing finance are more likely to have females as their top managers. However, for the South Caucasus region, there was no gender difference. Research limitations/implications: This research is based on evidence from the Baltic States and the South Caucasus region. However, the findings are relevant to discussions on the importance of the context of entrepreneurship, and more specifically, the rule of law. The institutional theory provides an explanation for coercive, normative and mimetic institutional isomorphism in the context of access to finance for SMEs. Coercive institutional isomorphism exerts a dependence on access to finance for SMEs. In coercive institutional isomorphism, formal and informal pressures are exerted by external organisations such as governments, legal regulatory authorities, banks and other lending institutions. These formal and informal pressures are imposed to ensure compliance as a dependency for successful access to finance goal. Practical implications: This research creates awareness among entrepreneurs, potential entrepreneurs, business practitioners and society that reducing obstacles to access finance and a fair court system improve entrepreneurial venture formation. This has the potential to create employment, advance business development and improve economic development. Originality/value: This paper makes an original contribution by emphasising the significance of access to finance and a fair court system in encouraging stronger entrepreneurship. The institutional framework provides a definition for coercive institutional isomorphism to show how external forces exert a dependence pressure towards access to finance for SMEs.